Factors That Influence the Ability to Perform Autologous Priming - Trowbridge, Cody (J Extra Corpor Technol, 2008)
The purpose of this study was to determine which factors impact the ability to perform autologous priming (AP) of the extracorporeal circuit. Second, the effects of differential AP on transfusion and volume requirements were evaluated. After institutional review board approval, demographic, operative, volumetric, and transfusion data were prospectively collected on 100 adult patients undergoing cardiopulmonary bypass (CPB). Two analyses were conducted: AP Taken and percent AP Given. For each analysis, three groups were created based on standard distribution. Group A included patients within less than mean – 1 SD (≤500 mL AP Taken or ≥90% AP Given back), group B included patients within mean ± 1 SD (501–1299 mL AP Taken or 11%–89% AP Given back), and group C included patients greater than mean + 1 SD (≥1300 mL AP Taken or ≤10% AP Given back). Weight, pre-CPB hematocrit, clinical severity, and pre-CPB volume balance did not differ between the groups. Significant differences existed in AP Taken and percent AP Given between individual perfusionists. More AP was given back with higher urine output (group A: 846 ± 700 mL, group B: 613 ± 414 mL, group C: 384 ± 272 mL; p = .004), more autotransfusion [group A: 0 (0,1300 mL), group B: 0 (0,500 mL), group C: 0 (0,250 mL); p = .008], and less AP Taken [group A: 800 (0,1300 mL), group B: 1000 (200,1600 mL), group C: 1000 (800,1600 mL); p = .001]. When more AP was taken, CPB hematocrit was higher (group A: 22.3% ± 4.8%, group B: 25.6% ± 4.7%, group C: 26.6% ± 4.3%; p = .032), and fewer patients received red blood cells (group A: 64.3%, group B: 28.3%, group C:14.3%; p = .017). Some perfusionists were able to remove more AP before CPB. When more AP was taken, CPB hematocrit was higher, fewer patients received a transfusion, and less AP was given back. More AP was also given back with higher urine output and higher blood loss to the autotransfusion device.